Synthesis of single phase brookite tio2 nanomaterials from different titanium complexes in application of methyl orange degradation and hydrogen evolution reaction - Vu, Viet Thang; Norbert, Steinfeldt; Ta, Duc Hong (Vietnam Journal of Science and Technology, 2025)
This research focus on preparation of brookite TiO2 materials from two different precursor as titanium glycolate and titanium lactate complexes. The single phase of brookite TiO2 is synthesized successfully by hydrothermal process and confirmed by the X-ray diffraction (XRD) results. The scanning electron microscope (SEM) analysis shows that the nanorod and cubic-like morphology of brookite TiO2 material are obtained by applying the titanium glycolate and lactate complex, respectively. The synthesized conditions are also investigated by changing the type and the amount of OH- sources. All the single phase brookite TiO2 samples are determined to contain a small amount of oxygen vacancies, which can by proved by the UV – Vis Diffuse reflectance spectroscopy (UV-Vis DRS) and X-ray photoelectron spectroscopy (XPS) measurement. The photoactivities of as-prepared brookite catalysts are tested in the application of methyl orange (MO) degradation and the hydrogen evolution reaction (HER), showing that the prepared cubic-like nanoparticle brookite sample Ti-NP-U9 exhibits higher activities compared with nanorod brookite TiO2 and even the commercial TiO2 P25. These results showing that the activity of brookite TiO2 is highly depended on the morphology and promising for further study to enhance the photocatalytic performance.Keywords: TiO2; brookite; nanorods brookite; cubic-like nanoparticles brookite; photodegradation; hydrogen evolution reaction